Creación de un tomo didáctico sobre expresión y comunicación, para personas con discapacidad visual, como herramienta educativa interactiva complementaria a la formación que reciben en el Instituto Mariana de Jesús - Arteaga Beltrán, Andrea Valeria (2020)
In this project, the volume ll of UPA, an educational tool collection, was developed for students with visual disabilities from Instituto Mariana de Jesús. This unit works as a complement to the learning of those from initial education, where it will help them to understand the information learned through sensoperception. The purpose of this work is to provide students of the institute with didactic tools, so they can get help in the area of expression and communication with the support of multimedia resources for guidance suitable to their needs. In the creation of this tool, proper materials were used for its applicability, complying with the requirements of the students, contributing to their education with topics that invite them to imagine how their body and face works, by using their other senses. As a result, the present work will serve as an aid in the educational area, easing the comprehension of different subjects for people with visual disabilities.